Age-specific associations of invasive treatment with long-term mortality of patients with acute myocardial infarction: Results of a real-world cohort analysis - Michael Kraus; Timo Schmitz; Dennis Freuer; Philip Raake; Jakob Linseisen; Christa Meisinger (International Journal of Cardiology: Heart & Vasculature)
Background: To investigate the age-specific association between invasive treatment, that is percutaneous coronary intervention (PCI) or coronary artery bypass graft (CABG) at acute myocardial infarction (AMI) and all-cause long-term mortality. Methods: The analysis was based on 4964 hospitalized AMI patients (age 25–84 years) registered by the population-based Augsburg Myocardial Infarction Registry between 2010 and 2017. The median follow-up time was 4.7 years (IQR: 2.7; 6.8). All-cause mortality was obtained by regularly checking the vital status of all registered AMI patients in cooperation with the regional population registries. In multivariable adjusted Cox regression analyses the age-specific associations between invasive therapy (PCI or CABG versus no invasive therapy) and all-cause mortality were investigated. Results: During follow-up 1224 patients (805 men and 419 women) died. In patients younger than 55 years 7.6 %, in the age group 55–64 years 7.1 %, in the age group 65–74 years 12.2 %, and in the age group 75–84 years 21.6 % did not undergo invasive therapy (PCI or CABG) during hospital stay. Invasive therapy using PCI or CABG significantly reduced mortality risk in all age-groups in comparison to AMI patients without invasive treatment. Even 75–84 years old benefited very impressively from invasive therapy regarding long-term all-cause mortality (PCI: HR 0.55; 95 % CI 0.44–0.70; CABG: HR 0.43; 95 % CI 0.30–0.62). Conclusions: Invasive or surgical therapy procedures in the treatment of AMI patients are effective in all age groups. Therefore, also old AMI patients should receive guideline-compliant therapy to achieve a better outcome.